Informal Spiritual Space (The Macau Ricci Institute Journal, 2020)
Inspired by Pope Francis's third encyclical letter “Laudato Si’, ” this paper analyses the significance of spiritual spaces, as well as the main causes and difficulties of the declining spiritual environment in modern society. As an architectural response to Pope Francis’s concern for the diminished role of spiritual places, this paper presents a theoretical study of the concept of “informal spiritual space” and proposes that formal spiritual space is not the only venue in which people may practice contemplation, and that an informal spiritual space can also build a symbolic connection with God, which represents God’s infinite beauty and goodness.